Using expatriates for adapting subsidiaries' employment modes to different market economies: a comparative analysis of US subsidiaries in Germany, the UK and Switzerland. (17th April 2019) - Meuer, Johannes; Kluike, Marlies; Backes-Gellner, Uschi; Pull, Kerstin
Because the extent to which multinational companies (MNCs) benefit from foreign subsidiaries depends on how effectively MNCs manage their foreign subsidiaries' workforce, the international management literature has long focused on how MNCs transfer Human Resource Management (HRM) practices. However, the literature has only vaguely dealt with institutional differences between host and home countries, often simplifying these differences under the umbrella of institutional or cultural distance. This article investigates how MNCs use expatriates to adjust subsidiaries' employment modes to different market economies. We define employment modes as bundles of HRM and industrial relations (IR) practices implemented at the firm level and examine the employment modes of 76 subsidiaries of US MNCs in a coordinated market economy (Germany), a hybrid market economy (Switzerland) and a liberal market economy (UK). Our results reveal substantial differences in the expatriation strategies of MNCs that depend not only on the international focus of the MNC but also on the differences in IR between the parent and subsidiary's environment. Our findings qualify the role of expatriates in adjusting subsidiaries' employment modes to different market economies and highlight the boundary conditions of integrating HRM with IR practices in the management of foreign subsidiaries.